Aproximaciones didácticas de la Enseñanza del Español como Lengua Extranjera (ELE) en Japón y Corea del Sur (2017)
This monograph identifies didactic categories of Spanish as a foreign language teaching (ELE) for students from South Korea and Japan, based on a documental analysis made up during the period of 1988-2016. This process allowed to demarcate the main panorama surrounding didactic processes that have been favored during the last decades in ELE for Korean and Japanese students, these are: ELE in isolated languages context, grammar in ELE and designs for ELE from interculturality and history. In conclusion, reflection core ideas are proposed from the categories that permit the formulation of didactic proposals in ELE along with the linguistic characteristics of the students.